Overview of relation between coverage of health services and maternal mortality in East Java Province in 2015 - Wahyul Anis; Kuntoro Kuntoro; Soenarnatalina Melaniani (Majalah Obstetri dan Ginekologi, 2016)
Objectives: to analyze the efforts of maternal health services that may affect maternal mortality rate.Materials and Methods: The study was conducted at the Health Office of East Java using secondary data from 38 districts/cities in East Java in 2015 that includes performance antenatal care K1 and K4, postnatal care, early detection of complications in pregnant women, natal in health workers and health facilities, management of complications by health workers and MMR. Data were analyzed with statistical method with spatial regression and illustrated with thematic maps by application ArcView statistics.Results: the highest MMR was in Bojonegoro district, Lumajang, Probolinggo, Bondowoso, Situbondo and Probolinggo city. Some districts/cities that have the highest maternal mortality has proximity of areas, namely the district Lumajang, Probolinggo, Bondowoso, Situbondo and Probolinggo city. Their proximity concluded an association condition and the causes of MMR between districts so they can be studied more in depth about the causes of MMR kind of social, cultural and geographical characteristics. The coverage maternal health services to all districts/cities in East Java province is not much difference.Conclusion: the maternal mortality rate in the district/city of East Java province in 2015 was not much affected by maternal health services so we need more research on other causes of MMR in districts/city of East Java Province.